Histology of non-glandular stomach in Southern red muntjac (Muntiacus muntjac) - Rajani, C. V.; Surjith, K. P.; Patki, H. S.; Raj, Indu V; Deepa, P. M.; S. Maya (Indian Journal of Veterinary Anatomy, 2024)
Southern red muntjac, also known as barking deer, is a small deer species classified under the family Cervidae. They are omnivorous animals and possess a four chambered stomach. Histomorphological studies on the non-glandular stomach of Southern red muntjac were conducted by using the specimens collected from three young and two adult animals. The tissue samples were processed for routine paraffin embedding procedures; sectioned, stained and microscopic features were recorded. Histologically, rumen presented characteristic papillae, reticulum with crests along with papillae and omasum with large wavy omasal folds. The reticular cells were undivided. The mucosa of non-glandular stomach comprising of rumen, reticulum and omasum were lined by keratinized stratified squamous epithelium. The lamina propria and submucosa layers were highly vascular in the three regions of non-glandular ruminant stomach. The apices of reticular crests enclosed muscularis mucosae, but it was entirely lacking in rumen. The lamina propria-submucosa was delimited by muscularis mucosae in Omasum. The central core of omasal folds enclosed a thick layer of circular smooth muscles in addition to the peripherally arranged muscularis mucosae. At the apices of omasal folds the muscularis mucosae interdigitated with the muscular layer. Tunica muscularis was composed of thick inner circular and thin outer longitudinal muscle layers. The serosa enclosed adipose tissue and nerve fibres. The histomorphological features of the non- glandular stomach suggested that the animals may be grouped under browsers.